HUBUNGAN PENGETAHUAN TENTANG GIZI SEIMBANG DAN POLA MAKAN DENGAN PRODUKSI ASI PADA IBU PRIMIPARA DI PUSKESMAS TUGU TAHUN 2022 - Melinda Dwi Ayu Handani (2022)
Breast milk production by optimizing breastfeeding for babies aged less than 6 months is still said to be insufficient. Lack of knowledge about balanced nutrition so that eating habits do not meet balanced nutrition resulting in the amount of breast milk secreted also not in accordance with the baby's needs. The purpose of the study was to determine the relationship between knowledge about balanced nutrition and eating patterns with breast milk production in primiparous mothers at the Tugu Health Center which was held from March to June 2022 using a cross sectional design. The population of this study was 172 with a sample of 131 respondents using a simple random sampling technique in the form of a questionnaire. Data analysis used univariate and bivariate with Chi Square statistical test. The results showed that 72.5% of breast milk production was insufficient. There is a relationship between family income (p = 0.001), knowledge of balanced nutrition (p = 0.029) and diet (p = 0.043) with breast milk production. To increase knowledge, it is necessary to promote health about balanced nutrition and maternal eating habits in accordance with the frequency of eating in order to have sufficient breast milk production.